The relationship between macroeconomic variables and small-and-medium-enterprises in Indonesia - Malik Cahyadin (Universitas Islam Indonesia, 2017)
This study analyses the interaction between macroeconomic variables and indicators of small and medium enterprises (SME) in Indonesia. The analysed data include GDP, inflation, unemployment, poverty number, the number of SME business units, total SME employment, and SME investment. It uses Granger Causality Test and VECM. It suggests that macroeconomic variables and SME indicators have one causal direction. In addition, there are short term and long term relationships between macroeconomic variables and indicators of SME. The response of macroeconomic variables for indicators of SME takes 4.5-5 years to stabilize. Meanwhile, the contribution of SME to GDP indicator is likely to increase from quarter 1 to 64.